Răspuns :
Răspuns:
Explicație pas cu pas:
1 .
a + b + c = 59
a = b : 3 => a = ( c - 10 ) : 3
b = c - 10
___________________
a = ?
b = ?
c = ?
___________________
Înlocuim :
[ ( c - 10 ) : 3 ] + ( c - 10 ) + c = 59 | • 3
( c - 10 ) + ( 3c - 30 ) + 3c = 177
7c - 40 = 177
7c = 177 + 40
7c = 217
c = 217 : 7
◇ c = 31
b = 31 - 10
◇ b = 21
a = 21 : 3
◇ a = 7
2 .
a + b + c = 55
b = a × 2
c = b + 15 => c = ( a × 2 ) + 15
_________________
a = ?
b = ?
c = ?
_________________
Înlocuim :
a + a × 2 + ( a × 2 ) + 15 = 55
5a + 15 = 55
5a = 55 - 15
5a = 40
a = 40 : 5
◇ a = 8
b = 8 × 2
◇ b = 16
c = 16 + 15
◇ c = 31
Răspuns:
1) dacă a=b:3 => b este de 3 ori mai mare decât a; dacă b=c-10=> c este mai mare cu 10 decât b. Rezolvarea in atasament
![Vezi imaginea Saoirse1](https://ro-static.z-dn.net/files/d0c/6390cae1f59e7c90e41d7b702b433070.jpeg)